The effect of rehabilitation exercises associated with local electrical stimulation according to the feeling of pain in the treatment of some cases of peripheral neuritis for women aged (50-55) years - Abd Al_Rasool Dagher, Raham (Journal of Physical Education, 2025)
The aim of the research was to develop rehabilitative exercises accompanied by electrical stimulation based on the perception of pain for women aged 50–55 years, and to identify the effect of these rehabilitative exercises accompanied by electrical stimulation—based on pain perception—on treating certain cases of peripheral neuropathy in women within the same age group. Accordingly, the researcher hypothesized that there would be statistically significant differences between the pre- and post-test results of the experimental group's electromyography (EMG) measurements, as well as statistically significant differences between the pre- and post-test results of pain level measurements using the Visual Analogue Scale (VAS) for the experimental group. The experimental research methodology was adopted using a one-group experimental design. The boundaries of the current research population were defined as women aged 50–55 years, with a total number of 9 patients who regularly attended the Al-Karkh Hospital / Physiotherapy Unit. All of them were deliberately selected using the comprehensive enumeration method, making up 100% of this population sample. The tests were determined, and rehabilitative exercises accompanied by electrical stimulation based on pain perception were designed. The experiment began with the pre-tests, followed by the implementation of these exercises. The duration of each rehabilitation session ranged from 28.5 to 32.36 minutes, with three sessions per week held on Sunday, Tuesday, and Thursday. Each session included four exercises and continued for eight consecutive weeks, resulting in 24 rehabilitation sessions. The experiment concluded with the post-tests. After processing the research results using the SPSS system, the conclusions and applications indicated that the rehabilitative exercises accompanied by electrical stimulation based on pain perception were suitable for women aged 50–55 years suffering from certain cases of peripheral neuropathy. These exercises had a positive effect on improving the EMG signals of the gastrocnemius muscles in both the right and left legs by increasing the peak level and reducing the spread area of the electrical signal. They also helped reduce pain levels as measured by the Visual Analogue Scale (VAS) in cases of peripheral neuropathy. It is essential to pay attention to the duration of the transitional rest period between electrical stimulation and the application of rehabilitative exercises based on pain perception when rehabilitating women aged 50–55 years with peripheral neuropathy. Furthermore, it is necessary to rely on the use of TENS (Transcutaneous Electrical Nerve Stimulation) current type when rehabilitating women in this age group to help reduce VAS-measured pain levels.